Ikaros Inhibits Group 3 Innate Lymphoid Cell Development and Function by Suppressing the Aryl Hydrocarbon Receptor Pathway - Li, Shiyang (Immunity, 2016)
Group 3 innate lymphoid cells (ILC3s) expressing the transcription factor (TF) RORγt are important for the defense and homeostasis of host intestinal tissues. The zinc finger TF Ikaros encoded by Ikzf1 is essential for RORγt(+) fetal lymphoid tissue inducer (LTi) cell development and lymphoid organogenesis, but its role in postnatal ILC3s is unknown. Here, we showed that small intestinal ILC3s had the lowest expression of Ikaros compared to ILC precursors and other ILC subsets. Ikaros inhibited ILC3s in a cell-intrinsic manner through zinc finger-dependent inhibition of transcriptional activity of the aryl hydrocarbon receptor, a key regulator of ILC3 maintenance and function. Ablation of Ikzf1 in RORγt(+) ILC3s resulted in increased expansion and cytokine production of intestinal ILC3s and protection against infection and colitis. Therefore, in contrast to its requirement for LTi development, Ikaros inhibits postnatal ILC3 development and function to regulate gut immune responses at steady state and in disease.